Pengaruh Net Sales dan Current Ratio terhadap Earning per Share (EPS) pada PT. Bumi Resources Tbk yang terdaftar di Jakarta Islamic Indeks (JII) - Liya Megawati (Politeknik Ganesha Medan, 2022)
This research is motivated by the assumption that Net Sales and Current Ratio affect Earning Per Share (EPS). It was stated by theory, namely when Net Sales rises and Current Ratio increases, Earning Per Share (EPS) increases, and vice versa if Net Sales decreases and Current Ratio decreases, Earning Per Share (EPS) decreases. The purpose of this study is to determine: (1) how much the influence of Net Sales have on Earning Per Share (EPS), (2) how much the influence of Current Ratio has on Earning Per Share (EPS), (3) how much the influence of Net Sales and Current Ratio to Earning Per Share (EPS) at PT. Bumi Resources Tbk. registered in the Jakarta Islamic Index (JII) for the period 2007 – 2016. The research method used is the descriptive analysis method with a quantitative approach which is analyzed partially, namely by simple regression analysis test, coefficient of determination, and t-test, and analyzed simultaneously with multiple regression analysis and F test. The data used in this study is data that is processed from the financial statements of PT. Bumi Resources Tbk.The results of this study show: (1) Net Sales has no significant effect on the Earning Per Share (EPS) of PT. Bumi Resources Tbk. accepted and the alternative hypothesis is rejected, (2) the alternative hypothesis which states that the Current Ratio has no significant effect on the Earning Per Share (EPS) of PT. Bumi Resources Tbk. accepted, (3) alternative hypothesis which states that Net Sales and Current Ratio have no significant effect on Earning Per Share (EPS) of PT. Bumi Resources Tbk. accepted. The result of the coefficient of determination is 17%. This shows that Earning Per Share (EPS) is influenced by the Net Sales and Current Ratio variables only by 17% and the remaining 83% is influenced by other factors outside of this study.